PELATIHAN DIGITAL MARKETING BAGI UMKM DI KELURAHAN PODOSUGIH UNTUK MENINGKATKATKAN PENJUALAN - Rustam Hanafi; sutapa; Mulyana (Dharma: Jurnal Pengabdian Masyarakat, 2026)
MSME actors in Podosugih Village generally have not yet optimized the use of marketplace platforms and social media for online sales, even though these platforms have great potential to attract consumers, especially the younger generation. In addition, their understanding of digital marketing concepts and practices as an effective and efficient marketing strategy remains limited. Based on these conditions, this community service program aims to provide training and assistance in digital marketing, particularly in the use of marketplaces and social media, so that MSME actors can improve their online selling capabilities. The training was attended by 29 MSME participants under the guidance of Podosugih Village. The implementation method consisted of three stages: (1) delivering materials to improve participants’ understanding and motivation regarding the importance of digital marketing; (2) hands-on practice involving the creation of accounts and product promotion through Shopee, TikTok, and Facebook; and (3) evaluation to measure participants’ levels of understanding and skills. The results indicate an improvement in participants’ comprehension of digital marketing concepts as well as their technical skills in using digital platforms. Quantitatively, many participants succeeded in creating or optimizing their marketplace and social media accounts. Qualitatively, participants demonstrated high enthusiasm and active involvement throughout the training activities. The three-stage approach used in this program can serve as an effective model for similar training initiatives in other MSME communities. Keywords: digital marketing, MSMEs, marketplace, social media, training